(untitled) (Bangladesh Journal of Otorhinolaryngology, 2015)
Historically, thyroid and parathyroid surgery was done initially under local anesthesia. With the advent of safer general anesthetic techniques, the need for local anesthesia fell dramatically. Recently the use of local anesthesia combined with monitored anesthesia care (MAC) has been reintroduced as an alternative to general anesthesia for some particular thyroidectomy. Newer intravenous anesthetic agents allow for the establishment of effective sedation and analgesia with adjusted level and duration of action. This allows for monitoring of the effectiveness of the anesthesia during the surgical procedure that meet the patients comfortable needs and the surgeons technical needs. This approach allows for rapid recovery of alertness and early assessment of the patients initial postoperative recovery. Additionally, it optimizes the potential for outpatient surgical care. We report a 25 year old male, diagnosed as a case of follicular adenoma of thyroid with emphysematous bullae; who had undergone thyroidectomy under local anaesthesia. Surgery was uneventful and resulted in a decreased length of stay, cost and operating time. DOI: http://dx.doi.org/10.3329/bjo.v20i2.22025 Bangladesh J Otorhinolaryngol; October 2014; 20(2): 93-97